2014
DOI: 10.1007/s10853-014-8429-3
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic and microwave absorbing properties of magnetite nanoparticles decorated carbon nanotubes/polyaniline multiphase heterostructures

Abstract: Magnetite nanoparticles decorated CNTs/PANI multiphase heterostructures were prepared by polymerization of aniline monomer and an additional process of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Recently, Zhang et al reported the electromagnetic and microwave absorbing properties of magnetite nanoparticles decorated carbon nanotubes/polyaniline multiphase heterostructures (CNTs/PANI/Fe 3 O 4 ). The results showed that under the optimum condition the largest reflection loss value of CNTs/PANI/Fe 3 O 4 multiphase heterostructures was À22.4 dB at 11.7 GHz with about 6.9 GHz bandwidth below À10 dB [51]. From the results what we discussed above, it can be seen that the leafletlike PEDOT/SWCNT composites possess good microwave absorbing property.…”
Section: Microwave Absorbing Propertiesmentioning
confidence: 61%
See 3 more Smart Citations
“…Recently, Zhang et al reported the electromagnetic and microwave absorbing properties of magnetite nanoparticles decorated carbon nanotubes/polyaniline multiphase heterostructures (CNTs/PANI/Fe 3 O 4 ). The results showed that under the optimum condition the largest reflection loss value of CNTs/PANI/Fe 3 O 4 multiphase heterostructures was À22.4 dB at 11.7 GHz with about 6.9 GHz bandwidth below À10 dB [51]. From the results what we discussed above, it can be seen that the leafletlike PEDOT/SWCNT composites possess good microwave absorbing property.…”
Section: Microwave Absorbing Propertiesmentioning
confidence: 61%
“…8a and b). These small peaks may be attributed to the interaction between PEDOT and SWCNTs [51]. Fig.…”
Section: Microwave Absorbing Propertiesmentioning
confidence: 94%
See 2 more Smart Citations
“…The electrical loss of HCl-PANi mainly came from the eddy current loss at the frequency of 2-7 GHz. 24 Interestingly, a broad dielectric response peak could be found at 10-16 GHz for the PANi/ ND-1 (see the supplementary material, Fig. S2(a) (Ref.…”
mentioning
confidence: 99%